Characteristic of individual indicators of phagocytic activity of leukocytes under conditions of formation of experimental contact dermatitis and experimental pneumonia and the effect of the drug thiotriazoline - Regeda-Furdychko, M. M. (Journal of Education, Health and Sport, 2019)
The work demonstrated, that polymorho-nuclear leucocytes take an active part in formation of experimental contact dermatitis and experimental pneumonia before and after administration of the antioxidant thiotriazoline and also testify to metabolic processes stimulation in leucocytes. The immune-modulating thiotriazoline preparation application, beginning from 8 th day of the experiment, and during 10 days, showed the renewal of indexes of phagocytar leucocytes' activity, the test of nitroblue tetrasolium, what testifies to its corregating action – on nonspecific resistance condition.